Mainstreaming public–private partnership in national development: How ready is Ghana?. Issue 3 (7th April 2019) - Ahenkan, Albert
Abstract: Public–private partnership (PPP) is a relatively new development paradigm in most developing countries. In an increasingly competitive global environment, governments around the world are focusing on new ways to finance development projects, build infrastructure, and provide social services to their citizens. This paper examines the challenges and the enabling environment for PPP mainstreaming in Ghana's development agenda. The study reviewed critical literature pertaining to prospects and challenges of PPPs across the world and critical success factors and challenges. The study was spiced by data generated through in‐depth interviews with experts on PPPs in Ghana. The paper reveals that implementation of PPPs in Ghana could be fraught with a number of challenges including regulatory frameworks, weak institutions, weak technical expertise, political will, bureaucracy, poor maintenance culture, contracting, negotiation challenges, and risk sharing and corruption. These challenges are complex in nature and require concerted effort and enabling environment to address them. There is the need for a clear regulatory framework and institutional capacity building to enable Ministries, Departments and Agencies and Metropolitan, Municipal and District Assemblies to effectively handle the PPP processes in Ghana.